Latest Results on Lattice Calculation Concerning K → πℓ+ℓ− Decays. (April 2020) - Boyle, P; Jüttner, A; HÓgáin, F Ó; Portelli, A
Abstract: The K → π ℓ + ℓ − decay is a flavor changing neutral current process which is forbidden at tree level in the Standard Model. This suppression causes the decay to be sensitive to potential New Physics. The decay channels are dominated by long-distance contributions, which require non-perturbative methods of investigation. Previous lattice calculations by the RBC and UKQCD collaborations, at unphysical kaon/pion masses, have successfully extracted the matrix elements needed to describe the form factor of the decays. A new lattice calculation, on a gauge configuration with m π ≈ 140 MeV and m K ≈ 500 MeV, is underway and will be discussed here.